1983
DOI: 10.1021/bi00292a009
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary aspects of accuracy of phenylalanyl-tRNA synthetase. Accuracy of fungal and animal mitochondrial enzymes and their relationship to their cytoplasmic counterparts and a prokaryotic enzyme

Abstract: Phenylalanyl-tRNA synthetases from mitochondria of yeast and hen liver resemble their corresponding cytoplasmic counterparts. Whereas slight intraspecies differences at the amino acid binding site, reflecting variations in the structures of these distinct enzymes, are exploitable by phenylalanine analogues, no intraspecies difference can be noted for the strategies to achieve the high fidelity of protein synthesis. While the yeast mitochondrial enzyme follows the pathway of posttransfer proofreading, the hen l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Mitochondrial PheRS is a chimera of the canonical a subunit with a C-terminal appendage containing the tRNA anticodon-binding domain (B8) of the canonical b subunit, but no putative editing domain. It was originally proposed that mitochondrial PheRSs are active in editing (Gabius et al, 1983), although later studies questioned the quality of the enzymes used in these studies (Sanni et al, 1991). Mitochondrial amino-acid pools are believed to be similar to those in the cytoplasm (Costantino and Attardi, 1973), suggesting that the need for editing mischarged Tyr would be similar in both compartments.…”
Section: Evolution and Retention Of Phers Editing Activitymentioning
confidence: 99%
“…Mitochondrial PheRS is a chimera of the canonical a subunit with a C-terminal appendage containing the tRNA anticodon-binding domain (B8) of the canonical b subunit, but no putative editing domain. It was originally proposed that mitochondrial PheRSs are active in editing (Gabius et al, 1983), although later studies questioned the quality of the enzymes used in these studies (Sanni et al, 1991). Mitochondrial amino-acid pools are believed to be similar to those in the cytoplasm (Costantino and Attardi, 1973), suggesting that the need for editing mischarged Tyr would be similar in both compartments.…”
Section: Evolution and Retention Of Phers Editing Activitymentioning
confidence: 99%
“…Despite their similarity to bacterial PheRSs, the mitochondrial versions do not contain regions analogous to the known editing domain (25). Although it was originally suggested that mitochondrial PheRSs were active in editing (28), later studies questioned the purity of the enzymes used for these studies (26). Here we describe an investigation of amino acid specificity and editing by mitochondrial and cytosolic PheRSs from the yeast Saccharomyces cerevisiae.…”
mentioning
confidence: 96%
“…These activities are readily separated by salting-out chromatography, and have a significantly different M r, which is not due to proteolytic degradation or partial dissociation under the conditions of gel filtration. Regarding the problem of the origin of cyanelles and plastids, this detection of 2 significantly distinct PRS involved in the expression of the 2 genomes within C. paradoxa is of considerable potential in establishing phylogenetic relationships, as described earlier using this system for yeast and liver mitochondria [8]. Considering the substrate specificity, it is thus reasonable to view the enzyme with M r 80 000 as a cyanelle enzyme.…”
Section: Discussionmentioning
confidence: 88%
“…Due to the fundamental role of PRS in protein biosynthesis, comparative studies on PRS have been used to trace the evolutionary process in other organisms [7][8][9]. We therefore initiated a study on the PRS activities found in C. paradoxa.…”
Section: Introductionmentioning
confidence: 99%